2013
DOI: 10.17221/9/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season and time of milking on spontaneous and induced lipolysis in bovine milk fat

Abstract: Toušová R., Stádník L., Ducháček J. (2013) The effects were evaluated of different factors on the level of spontaneous (SPO) and induced (IND) lipolysis as defined by the content of free fatty acids (FFA) in milk. Milk samples were collected at monthly intervals throughout the year from both morning and evening milkings either individually in a milking parlour (SPO; n = 10) or from the bulk tank (IND; n = 10). The data were analysed using SAS 9.1. More intensive SPO was observed from March to May with higher F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Our findings corresponded with stated range as well as were in accordance with Toušová et al (2013) who detected higher value of FFA content in milk from induced lipolysis compared to spontaneous ones.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings corresponded with stated range as well as were in accordance with Toušová et al (2013) who detected higher value of FFA content in milk from induced lipolysis compared to spontaneous ones.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, the number of FFA in raw milk also depends on the size of the damaged fat globules as an indicator of lipolysis. We can describe two types of lipolytic changes in raw milk -spontaneous and induced lipolysis (Toušová et al, 2013). Spontaneous lipolysis is a natural and spontaneous process in the raw milk after milking influenced by the cow's individuality, level and compound of feed ratio (Chilliard et al, 2003;Cieslak et al, 2010), milking frequency (Wiking et al, 2006), energy balance (González et al, 2011) and by the microorganisms activity (Vyletělová et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is a rich source of the saturated fatty acids. Milk fat consists of triacylglycerol, phospholipids, non-esterified fatty acids, and glycerol (Toušová et al, 2013). Researchers have demonstrated that milk fat contains components having positive impact on health and proved to be effective against cancer or coronary heart disease like atherosclerosis.…”
mentioning
confidence: 99%
“…Lipomobilisation increases free fatty acid plasma content and triacylglycerol accumulation in the liver tissue affecting its structure and function (Shibano & Kawamura 2006;Jóźwik et al 2012). Milk fat consists of individual fatty acids (FA) and their triglycerides as the main components influenced by animal species or rather breed (Pešek et al 2005;Marounek et al 2012), cow's individuality (Stádník & Louda 1999;Soyeurt et al 2006), parity , nutrition level (Kupczyński et al 2012), milk yield (Kay et al 2005), and season as well as milking time (Toušová et al 2013).…”
mentioning
confidence: 99%